Morphology of Richards' gland in the swarm-founding wasp (Hymenoptera, Vespidae) - Da Silva, Marjorie [UNESP]; Noll, Fernando Barbosa [UNESP]; Billen, Johan (Wiley, 2014)
Richards' gland is known for the majority of Epiponini wasps, and despite few experimental evidences, the taxonomic distribution in swarm-founder species and the function of this gland remain rather unclear. This work presents a morphological description of Richards' gland in Protonectarina sylveirae. The gland is formed by a cluster of class 3 cells underneath the anterior margin of the fifth metasomal sternite, and a reservoir formed by the intersegmental membrane between the fourth and fifth metasomal sternites where the secretion can be stored. The secretory cells contain a branched end apparatus that carries the secretory products towards the duct cell. Externally, the cuticle of the sternite, where the duct cells penetrate, is characterized by modifications as scales with very numerous pores. The presence of Richards' gland according to the model proposed by Samacá et al. 2013 in Protonectarina corroborates the single origin of this gland in Epiponini. The occurrence of a Golgi apparatus and smooth endoplasmic reticulum suggests pheromone production.
Keywords: Epiponini; exocrine glands; swarming; fifth sternite gland